1987
DOI: 10.1037/0022-006x.55.6.805
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and infant temperamental predictors of attachment: A meta-analytic review.

Abstract: Because of the possible implications of infant-mother attachment for later adjustment, we examined the extent to which it could be predicted by mother interactional variables and infant proneness to distress. The meta-analysis demonstrated that sensitive, responsive maternal interaction predicted the security of attachment in Ainsworth and Wittig's (1969) "strange situation." However, the strength of the relation was less than many narrative reviews have suggested. Proneness to distress, which is conceptualize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
216
6
9

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(246 citation statements)
references
References 37 publications
11
216
6
9
Order By: Relevance
“…Mothers of difficult boys returned to work earlier than mothers of difficult girls, and mothers with lower AFQT scores were more likely to work if the child was a boy; preexisting differences in maternal ability and infant temperament may explain some reported gender differences in daycare outcome (Rutter, 1981;Bronfenbrenner et al, 1984;Gamble and Zigler, 1986;Goldsmith and Alansky, 1987;Hoffman, 1989, Desai et al, 1989, and NICHD, 1997. )…”
Section: Discussionmentioning
confidence: 99%
“…Mothers of difficult boys returned to work earlier than mothers of difficult girls, and mothers with lower AFQT scores were more likely to work if the child was a boy; preexisting differences in maternal ability and infant temperament may explain some reported gender differences in daycare outcome (Rutter, 1981;Bronfenbrenner et al, 1984;Gamble and Zigler, 1986;Goldsmith and Alansky, 1987;Hoffman, 1989, Desai et al, 1989, and NICHD, 1997. )…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Sroufe (1985) has argued that while temperament must be considered an important contributor to the mother-infant relationship, temperament per se is unimportant in explaining the construct of attachment itself. Others hold a more moderate position (e.g., Belsky & Rovine, 1987;Seifer, Schiller, Sameroff, Resnick, & Riordan, 1996;Stams, Juffer, & van IJzendoorn, 2002;Teti, Nakagawa, Das, & Wirth, 1991;Vaughn et al, 1992), and in a meta-analysis it was concluded that infant temperament variables are associated with attachment status to a similar degree as is maternal sensitivity (Goldsmith & Alansky, 1987). Together, these contentions suggest that temperament may be a confound in studies exploring relations between attachment status and variables of interest.…”
mentioning
confidence: 88%
“…Because past research has shown that the infant temperament variable is associated with infant attachment status (Goldsmith & Alansky, 1987), dyadic synchrony (Vizziello, Ferrero, & Musicco, 2000), and with maternal behavioral sensitivity (e.g., Crockenberg & McClusky, 1986;Mangelsdorf, Gunnar, Kestenbaum, Lang, & Andreas, 1990) and sensory sensitivity (Donovan et al, 2005a;2005b), the temperament measures, ITQ and ECBQ, were initially entered as control variables in Step 1 of each regression analysis. The entry of the ECBQ measure was found to improve the significance of all the predictor variables, including sensory sensitivity for which its entry was necessary to obtain significance.…”
Section: Predictors Of Maternal Toddler and Dyadic Interaction Durimentioning
confidence: 99%
“…Sufficient numbers of studies were available for testing the association between AQS and SSP (k 5 32), AQS and sensitive responsiveness (k 5 42), AQS and temperament (k 5 27), and AQS and socioemotional development (k 5 33). Earlier meta-analyses in the area of attachment were based on similar or smaller numbers of studies (e.g., Fox, Kimmerly, & Schafer, 1991;Goldsmith & Alansky, 1987;Van IJzendoorn, 1995).…”
Section: Selection Of Studiesmentioning
confidence: 99%